"Brain-Coral-Like" Mesoporous Hollow CoS2@N-Doped Graphitic Carbon Nanoshells as Efficient Sulfur Reservoirs for Lithium-Sulfur Batteries - Seo, Seung-Deok; Park, Dongjoo; Park, Sangbaek; Kim, Dong-Wan (WILEY-V C H VERLAG GMBH, 2019)
Hollow carbon materials are considered promising sulfur reservoirs for lithium-sulfur batteries owing to their internal void space and porous conductive shell, providing high loading and utilization of sulfur. Since the pores in carbon materials play a critical role in the infusion of sulfur, access of the electrolyte, and the passage of lithium polysulfides (LPSs), the creation and tuning of hierarchical pore structures is strongly required to improve the electrochemical properties of sulfur/porous carbon composites, but remains a major challenge. Herein, a "brain-coral-like" mesoporous hollow carbon nanostructure consisting of an in situ-grown N-doped graphitic carbon nanoshell (NGCNs) matrix and embedded CoS2 nanoparticles as an efficient sulfur host is presented. The rational synthetic design based on metal-organic framework chemistry furnishes unusual multiple porosity in a carbon scaffold with a macrohollow in the core and microhollows and mesopores in the shell, without the use of any surfactant or template. The CoS2@NGCNs/S composite electrode facilitates high sulfur loading (75 wt%), strong adsorption of LPSs, efficient reaction kinetics, and stable cycle performance (903 mAh g(-1) at 0.1 C after 100 cycles), derived from the synergetic effects of the dual hollow features, chemically active CoS2, and the conductive and mesoporous N-doped carbon matrix.
Keywords: COBALT SULFIDE; ZIF-67; POLYHEDRA; SHELL; POLYSULFIDE; HETEROSTRUCTURES; FABRICATION; PYROLYSIS; NANOTUBES; FRAMEWORK